RESPON SISWA TERHADAP PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA MATERI KALOR DAN PERPINDAHANNYA - Mufidatul Hasanah; Tutut Nurita (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
This study aims to determine students' responses to the application of guided inquiry learning models on heat material and its displacement. This research uses qualitative research using literature review method. The research instrument used a student response questionnaire distributed to 30 MTs students. The data collection techniques used were in the form of interview techniques and questionnaire techniques for student responses to the application of the guided inquiry learning model. The data obtained in this study will be analyzed by calculating the percentage results of each student response questionnaire result, so that the positive and negative responses of students are known. The results obtained showed more positive responses than students' negative responses to the application of the guided inquiry model, positive responses were almost obtained in every statement except in statement 8 regarding students having no difficulty when making hypotheses / assumptions while in books and student worksheets obtained a balanced response between positive response and negative response